The Necessity Of Activating The Foresight To Improve The Image Of The Institution Through The Duffy Approach To Knowledge Management: A Field Study For A Sample Of Banks In Algeria - BENAROUS, DJAMEL; AL-ENEZI, HAMOOD; Hima, Nadia; LOUAIL, BILAL (The journal of contemporary issues in business and government, 2021)
The study looked at the effects of foresight on the organization's image through the Duffy approach to knowledge management (Strategy, Tools, Individuals, Operations). To test the field framework, and using techniques for modelling structural equations (route analysis) have been applied to data collected from 154 individuals at the management levels of a group of banks in banking. The results of the study indicate that the relationship between the outlook and the organization's image is positively linked through the knowledge management approach, which has a more substantial impact on the organization's image, and the study concluded that the strategic foresight of the institutions under consideration in the increased interest in managing their intellectual skills would improve the image and impact of their brands.